Caffey’s Disease Affecting the Ribs - Nayek, Kaustav; Barik, Kanailal; Chaki, Bhusan; Adhikary, Amit (Journal of Nepal Paediatric Society, 2013)
Caffey’s disease is a rare disorder affecting the bones in infancy. It is characterized by irritability, fever, cortical hyperosteosis and adjacent soft tissue swelling. Here is report of an uncommon case where the ribs were significantly affected including the clavicle. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6933 J. Nepal Paediatr. SocVol.32(3) 2012 250-251